Identifikasi Keragaman Gen TGF-β2 dan Asosiasinya dengan Sifat Pertumbuhan pada Ayam Tolaki - M. Akramullah; C. Sumantri; N. Ulupi; M. A. Pagala (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The transforming growth factor-beta 2 (TGF-β2) gene is a group of growth hormone (GH) genes that control the nature of growth and belongs to the cytokine group. This study aimed to identify Single Nucleotide Polymorphism (SNP) g.640 T>C from the TGF-β2 gene then associated with the growth properties of tolaki chickens. Chicken blood samples used in this study amounted to 70 birds. Data on the nature of growth observed include; hatched weight, feed consumption, body weight, body weight gain and feed conversion. The TGF-β2 gene polymorphism was identified using the PCR-RFLP method. SNP g.640 T>C in the TGF-β2 gene was polymorphic and wasin Hardy-Weinberg balance. Identification results found 2 alleles, namely T and C and 3 genotype namely TT, TC, and CC. The association of TGF-β2 gene diversity in tolaki chicken generally showed a difference (P<0.05) on feed consumption, body weight and body weight gain. CC genotype has higher feed consumption, body weight, weight gain and more efficient feed conversion than TC and TT genotypes.